1977
DOI: 10.1007/bf00426480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzodiazepines on central serotonergic neuron systems

Abstract: Intracerebral (i.c.) injection of serotonin (5-HT) into mice induced head twitches in a dose-dependent manner at 10 min after injection. The head twitches induced by 5-HT (i.c.) were potentiated by the pretreatment of isocarboxazid (3 mg/kg i.p.), and inhibited by cyproheptadine (0.3 mg/kg i.p.), a 5-HT antagonist. Benzodiazepines such as fludiazepam and diazepam potentiated the head twitches induced by 5-HT (i.c.) in a dose-dependent manner. Mescaline (50 mg/kg i.p.) also induced head twitches in mice at 15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Benzodiazepine receptor ligands showed the expected profile. Diazepam potentiated head-twitching (as reported by Nakamura & Fukushima, 1977) and the 'inverse agonist' PCCE (Polc et al, 1982) inhibited it. Rol 5-1788 is a benzodiazepine with antagonistic effects against both classic benzodiazepines and 'inverse agonists' (Hunkeler et al, 1981).…”
Section: Discussionmentioning
confidence: 76%
“…Benzodiazepine receptor ligands showed the expected profile. Diazepam potentiated head-twitching (as reported by Nakamura & Fukushima, 1977) and the 'inverse agonist' PCCE (Polc et al, 1982) inhibited it. Rol 5-1788 is a benzodiazepine with antagonistic effects against both classic benzodiazepines and 'inverse agonists' (Hunkeler et al, 1981).…”
Section: Discussionmentioning
confidence: 76%
“…In addition, they showed that the BZs did not change the uptake of 5-HT into the synaptosomal fraction in the rat brain. From these results, Nakamura and Fukushima [19] suggested that the HTR induced by BZs might directly act on the 5-HT receptor. Furthermore, Fuxe et al [20] also reported that 5-HT uptake by a slice of cerebral cortex was largely not affected by BZs such as diazepam.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, based on these results, it can be assumed that the possible mechanism of HTR induction by BZRAs is similar to the mechanism of the HTR induction by both p-hydroxyamphetamine and ·-methylated tryptamine derivatives such as 5-fluoro-·-methyl-tryptamine and 6-fluoro-·-methyl-tryptamine [16]. Nakamura and Fukushima [19] reported that BZs such as fludiazepam and nitrazepam induced HTR in mice, and that the responses of BZs were inhibited by cyproheptadine, a 5-HT receptor antagonist. In addition, they showed that the BZs did not change the uptake of 5-HT into the synaptosomal fraction in the rat brain.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that moderate to high doses of benzodiazepines can potentiate headtwitches induced in mice by 5-hydroxytryptamine (5-HT) receptor agonists such as 5-HT itself, 5-methoxy-N,N-dimethyltryptamine (5-MeODMT), quipazine, and mescaline [Nakamura and Fukushima, 1977;Singh et al, 1986;Moser and Redfern, 19881. In ad-dition, certain benzodiazepines have been reported to induce head-twitches [ Nakamura and Fukushima, 1976;Boissier and Dumont, 19811, although this is not a consistent finding [Moser and Redfern, 19881.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that moderate to high doses of benzodiazepines can potentiate headtwitches induced in mice by 5-hydroxytryptamine (5-HT) receptor agonists such as 5-HT itself, 5-methoxy-N,N-dimethyltryptamine (5-MeODMT), quipazine, and mescaline [Nakamura and Fukushima, 1977;Singh et al, 1986;Moser and Redfern, 19881. In ad-dition, certain benzodiazepines have been reported to induce head-twitches [ Nakamura and Fukushima, 1976;Boissier and Dumont, 19811, although this is not a consistent finding [Moser and Redfern, 19881. The mechanisms involved in this effect of benzodiazepines remain obscure although there have been several suggestions, such as GABAergic modulation of head-twitch behavior, a direct linkage between benzodiazepine receptors and 5-HT, receptors [ Nakamura and Carney, 19831, or a direct effect of benzodiazepines on 5-HT, receptors [Nakamura and Fukushima, 19771. The modulation of head-twitch behavior by GABAergic mechanisms has been extensively studied but the results have been inconsistent, and different laboratories have reported opposite results with several compounds [e.g., Handley and Singh, 1985;Metz et al, 1985;Moser and Redfern, 19881.…”
Section: Introductionmentioning
confidence: 99%